Transparencia en la gerencia de empresas constructoras (2017)
Managements as heads of the productive apparatuses of our economies have a definitive role in decision-making. This consideration has influenced to propose an investigation in the Business Management, where one of the central issues is represented in the analysis of ethics and decision-making under the principles of transparency in the construction sector, and we will establish critical aspects and control activities in each of the processes that make up an ethical business culture.